Mix design of high-performance concrete - Aminul Islam Laskar (Materials Research, 2011)
A mix design procedure for high-performance concrete mixes has been presented in this paper. Since rheological parameters and compressive strength are fundamental properties of concrete in two different stages of production, the correlation between rheological parameters and compressive strength has been used instead of using water-cement ratio versus compressive strength relationship. Water-cement ratio and aggregate volume to paste volume ratio has also been determined from rheological behavior and used in the mix design. In the proposed method, the designer is able to estimate rheological parameters like yield stress and plastic viscosity at the design stage for a given target strength, in addition to ingredients of concrete.